Human-machine symbiosis: A multivariate perspective for physically coupled human-machine systems. Issue 170 (February 2023) - Inga, Jairo; Ruess, Miriam; Robens, Jan Heinrich; Nelius, Thomas; Rothfuß, Simon; Kille, Sean; Dahlinger, Philipp; Lindenmann, Andreas; Thomaschke, Roland; Neumann, Gerhard; Matthiesen, Sven; Hohmann, Sören; et al.
Highlights: The paper discusses the varied usage of the term "symbiosis" in human-machine interaction. A multivariate approach for the description of symbiosis as the highest form of physically coupled human-machine systems is proposed. Four dimensions are proposed: task, interaction, performance and experience, which are elaborated from an interdisciplinary point of view. An example of human-machine symbiosis is given and described using the framework consisting of the proposed dimensions. Abstract: The notion of symbiosis has been increasingly mentioned in research on physically coupled human-machine systems. Yet, a uniform specification on which aspects constitute human-machine symbiosis is missing. By combining the expertise of different disciplines, we elaborate on a multivariate perspective of symbiosis as the highest form of interaction in physically coupled human-machine systems, characterized by a oneness of the human and the machine. Four dimensions are considered: Task, interaction, performance, and experience. First, human and machine accomplish a common objective by completing tasks conceptualized on a decomposition, a decision and an action level (task dimension). Second, each partner possesses an internal representation of the oneness they form, including the partner's inner states (e.g. experiences) and their joint influence on the environment. This representation constitutes the "symbiotic understanding" between both partners, being the basis of a joint and highly coordinated action (interaction dimension). Third, the symbiotic interaction leads to synergetic effects regarding the complementary strengths of the partners, resulting in a higher overall performance (performance dimension). Fourth, symbiotic systems specifically change the user's experiences, like flow, acceptance, sense of agency, and embodiment (experience dimension). Our multivariate perspective allows a clear description of symbiotic human-machine systems and helps to bridge barriers between different disciplines.